PENGARUH MODEL PEMBELAJARAN CREATIF PROBLEM SOLVING (CPS) BERBANTUAN MEDIA DIORAMA TERHADAP HASIL BELAJAR IPA KELAS V SDN 10 SURAU GADANG - Rahma; Marfilinda, Riri; Apfani, Sry (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low science learning outcomes of fifth grade students at SDN 10 Surau Gadang. This issue stemmed from a lack of orderliness during lessons as many students played around rather than focusing and a lack of variety in the instructional media used. The study aimed to determine the effect of the Creative Problem Solving (CPS) learning model, supported by diorama media, on the science learning outcomes of fifth-grade students at SDN 10 Surau Gadang. A quasi-experimental design was employed, specifically the Nonequivalent Posttest-Only Control Group Design. The study population consisted of all fifth grade students at the school, with Class VA serving as the experimental group and Class VB as the control group; a saturated sampling technique was used. Data were collected via tests, utilizing an objective instrument consisting of multiple choice questions. Hypothesis testing was conducted using the t test statistic, preceded by normality and homogeneity tests at a significance level of 0.05. Posttest results revealed that the experimental class achieved a higher mean score 78 compared to the control class 65. Hypothesis testing yielded a t-calculated value of 2.611 and a t-table value of 2.035; since t-calculated > t-table, the null hypothesis H0 was rejected and the alternative hypothesis H1 was accepted. The study concludes that the application of the Creative Problem Solving (CPS) learning model, supported by diorama media, positively influences the science learning outcomes of fifth grade students at SDN 10 Surau Gadang. Keywords: Creative Problem Solving (CPS), Diorama, Learning Outcomes, Science.